Hubungan Supervisi Kepala Ruangan Dengan Motivasi Kerja Perawat Di Ruang Rawat Inap - Dita - Purnamasari; Erwin - -; Jumaini - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine relationship between nurse unit manager supervision with motivation of nurses in Ward RSUD Arifin Achmad Provinsi Riau. This research used descriptive correlative method with cross sectional approach. The research was conducted at RSUD Arifin Achmad Provinsi Riau by total sample of 43 people who were taken by using a random sampling technique. Measuring instrument used was questionnaire which tested the validity and reability. The analysis used chi-square test. The results of this research showed no relationship between supervision by nurse unit manager with motivation of nurses in Ward (p value 0,169 > a 0,05). From this research,it  is expected to hospital management to evaluate the implementation of nurse unit manager supervision and to improve the supervision of the nurse unit manager so that the supervision of the implementation of the objectives and benefits of supervision can be achieved.   Keywords              : motivation of nurses, nurse unit manager, supervision. Reference : 46 (1987-2013)